Studi Literatur tentang Riset Zakat - Aam Slamet Rusydiana; Salman Al Farisi (AHKAM : Jurnal Ilmu Syariah, 2016)
Literature Study on Zakah Research. Zakah is not only as religious rituality but also could touch humanity aspect by empowering its potency to maximize public wealth. The research related to zakah is still lacking compare to Islamic banking research. This study review on research around zakah. The study use descriptive statistical analysis based on 100 journal publications related to zakah, both national and international journal. The entire sample journal publications have published last 5 years from 2011 to 2015. Results show that the zakah research is still dominated by the discussion of zakah institution (26%), followed by distribution of zakah(22%), zakah management (21%) and poverty (20%). The last theme is about zakah collection (11%). In addition, comparison of quantitative research and mixed methods are still far less than the qualitative approach.DOI: 10.15408/ajis.v16i2.4458